2022
DOI: 10.1038/s41467-022-32871-3
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-derived lactate is a signalling metabolite that potentiates adipose macrophage inflammation via targeting PHD2

Abstract: Adipose tissue macrophage (ATM) inflammation is involved with meta-inflammation and pathology of metabolic complications. Here we report that in adipocytes, elevated lactate production, previously regarded as the waste product of glycolysis, serves as a danger signal to promote ATM polarization to an inflammatory state in the context of obesity. Adipocyte-selective deletion of lactate dehydrogenase A (Ldha), the enzyme converting pyruvate to lactate, protects mice from obesity-associated glucose intolerance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 59 publications
3
36
0
1
Order By: Relevance
“…Augmented lactate levels in adipose tissue and plasma are widely reported in obese/diabetic subjects (Krycer et al, 2020;Feng et al, 2022). Metabolically, we found that FXN-deficient adipocytes have increased glycolytic activity and consequent hyperproduction of lactate.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Augmented lactate levels in adipose tissue and plasma are widely reported in obese/diabetic subjects (Krycer et al, 2020;Feng et al, 2022). Metabolically, we found that FXN-deficient adipocytes have increased glycolytic activity and consequent hyperproduction of lactate.…”
Section: Discussionsupporting
confidence: 53%
“…Lactate was previously regarded as the waste product of glycolysis. Recently, it has emerged that lactate serves as a danger signal that promotes polarization of resident macrophages towards a pro-inflammatory M1-like state in the context of obesity (Feng et al, 2022;Lin et al, 2022). Based on this evidence and our RNAseq results, we determined the leukocyte abundance in SVCs isolated from vWAT.…”
Section: Figure 1 Alteration Of Gene Expression In Vwat Of Kiko Mice A)mentioning
confidence: 95%
See 1 more Smart Citation
“…Adipose tissue is a structurally heterogeneous endocrine organ that consists of fat cells (adipocytes) and their precursors (preadipocytes) [38], as well as fibroblasts, endothelial cells, vascular cells [10], resident immune cells (predominantly macrophages) [39], and neuronal cells [40]. These different cell types are essential for the physiological role of the adipose tissue, but they often interact in the pathophysiological complications of obesity.…”
Section: Role Of Pi3k/akt In Adipose Tissuementioning
confidence: 99%
“…Additionally, lactate interacts with NDRG Family Member 3 (NDRG 3) to protect it from ubiquitination degradation and response to hypoxia. In adipose macrophages, the adipocyte‐derived lactate binds to prolyl hydroxylase domain containing 2 (PHD2) to promote adipose inflammation and insulin resistance (T. Feng et al, 2022). Collectively, these findings indicate that these receptors/sensors can not necessarily explain every physiological phenomenon mediated by lactate, and there should be yet‐undiscovered receptors/sensors linked with lactate signaling.…”
Section: Lactate Signalingmentioning
confidence: 99%